INDIA’S POSITION IN THE INTERNATIONAL ARENA: THE ONTOLOGICAL SECURITY PERSPECTIVE - JANUŠEVSKA, AGNĖ (Politologija, 2012)
India is a rapidly growing democratic naval power. Moreover, its features such as the strong and fast-growing economy, newest military technologies and nuclear weapon make a big impression. Considering the other major powers, it seems that the world is becoming multipolar where India could have a significant role and become one of the major poles. It has been a subject for discussions among journalists and academics for a log time. On the other hand, there are a lot of discussions about India’s “friendly and mild” foreign policy; also, it is sometimes named the non-ambitious passive player in the international arena. The optimism with doubts: the paradoxical situation composed of the history of the impressive imperial civilization, modern-day economic growth, huge progress in technologies versus the major internal problems and “soft” state image. Here emerges the problem: why India’s foreign policy, despite its power growth, is still passive/neutral on the international arena? The hypotheses to answering this question are: 1. India’s role and status are restricted by its lack of power. 2. India’s role on the international arena is restricted by its ideological and neutrality traditions, which provide ontological security to India. The aim of this article is to ascertain and explore India’s status (regional or global) and to ascertain India’s role (self-identification) on the international arena by using the ontological security theory. The theoretical background of this essay is ontological security theory which ten years ago was absorbed from sociology and is quite new in the international relations and security studies. Its main arguments are: ontological security is the security of being; in addition to physical security, states also seek ontological security (security of the self); ontological security is achieved by routinizing relationships with significant others, after all players become attached to those relationships, even if they are dangerous to their physical security. This theory is strongly bound with the identity that India always gives the self culture prominence in its discourse and its friendly discourse in the Ministry of Defence annual reports. This is the reason why the ontological security theory was chosen to help understand and explain India’s foreign policy. First, links between ontological and traditional security are discussed in the first part of this work. There is a broad analysis of the assumptions of the ontological security theory in the same paragraph. Second, there is a short criticism of the ontological security. Finally, the ontological security theory as the India’s foreign policy explanation tool is discussed; the discourse analysis is introduced as a methodological instrument of the work, and the model of analysis of the second part of the work, is defined. The second part of the work contains the content analysis of experts’ articles and official documents of India’s Foreign Ministry, using the model defined in the previous part and ontological security for the results’ explanation. The analysis made in the second part of the work has shown that the ontological security theory is able to explain India’s foreign policy and does it. The first hypothesis (India’s role and status are restricted by its lack of power) was denied. This means that India can be a major global power. The second hypothesis (India’s role in the international arena is restricted by its ideological and neutrality traditions, which provide ontological security to India) was approved. Strictly, it means that India does not want to be a major power because of it self-identity and ontological security. India does not expose itself as a major power but thinks that is worth to be such. On the other hand, if India has absorbed the international politics routine form the British Empire, this could mean that India’s identity is to be a global power, but it does not want to publicise it yet. The study has shown that it is hard to regard India in the international community as a major power without special observation or using just the realism theory tools. Consequently, the ontological security theory has shown that it has the tools that can be used in countries’ foreign policy explanation.